Surgical site infection rate is lower in laparoscopic than open colorectal surgery. - Howard, D; Datta, G; Cunnick, G; Gatzen, C; Huang, A (2010)
OBJECTIVE: Few studies have investigated whether surgical site infection (SSI) incidence differs between laparoscopic colorectal surgery (LCS) and open colorectal surgery (OCS). This study investigated the SSI incidence using the validated UK SSI Surveillance Service (SSISS) criteria for diagnosing wound infections. METHOD: Prospective data collection recorded patients' demographics, operative details, antibiotic use, wound evaluation and microbiological wound culture results, for consecutive patients undergoing elective resectional LCS and OCS. Postdischarge surveillance consisted of patient questionnaires sent out at 30 days and the primary care communication. RESULTS: A total of 122 patients underwent colorectal resections over 1 year (LCS 43; OCS 79). Patients' demographics and operative case-mix were similar for both groups, including body mass index (BMI), diabetic and smoking status. Operative duration was longer in the LCS group compared with OCS group (P = 0.012, Mann-Whitney U-test), but hospital stay was shorter for LCS (P = 0.0001, Mann-Whitney U-test). The SSI rate was significantly lower in the LCS than OCS group (7%vs 25% respectively; P = 0.015, two-tailed Fisher's exact test). BMI > 30 and operation length > 4 h influenced the risk of SSI formation (P < 0.05, chi-squared test). One LCS patient required conversion to a limited laparotomy. CONCLUSIONS: Surgical site infection incidence is significantly lower following LCS when compared with OCS. Confounding factors in this study include patient selection for LCS and nonrandomization.